Development of a questionnaire for problematic social networking sites use: Ensuring content validity through Delphi methodology - Seungju Lim; Ji-Hyuk Park (PLoS ONE, 2025)
Objectives This study aimed to develop a questionnaire to assess problematic social network service use (PSNSU) applicable to both adolescents and adults to ensure content validity. Methods A Delphi survey methodology with a panel of 16 experts was employed from April to June 2024 to ensure the content validity of the PSNSU assessment tool. This study involved three rounds of Delphi surveys to collect both open- and closed-ended responses to the PSNSU questionnaire. Data analysis focused on calculating the content validity ratio (CVR), stability, and consensus of each item. Items that did not meet the threshold criteria were revised or removed based on expert feedback. Results The PSNSU questionnaire initially included three domains and 59 items. Following Round 1 of the Delphi survey, three domains, 11 subdomains, and 43 items were selected. After adding and modifying the domains and items, Round 2 resulted in a questionnaire with two domains, 10 subdomains, and 42 items. In Round 3, the revised PSNSU questionnaire showed an average CVR of 0.99, a stability of 0.10, and consensus of 0.97, thus concluding the Delphi process. Conclusions The final PSNSU questionnaire encompasses a wide range of issues related to addictive behaviors and occupational challenges. Content validity was validated through the Delphi survey, resulting in a comprehensive tool that reflects the multidimensional characteristics of PSNSU across different life stages. This tool can be used for both clinical assessments and research to better understand and address PSNSU.